MILITARY IN LEADERSHIP SUCCESSION - Habbodin, Muhtar (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This article aims to explain the presence of the military in the succession of national leadership. The military's presence in the succession of leadership shows that power is a contested item between civilian leaders and military leaders. Through direct elections, both the military and civilians have the opportunity to become national leaders. However, only one will be the winner. This is aimed at Prabowo's victory in leadership succession. The 2024 leadership succession equals the superiority of the military over civilian politicians. Prabowo's victory sparked the return of military political power. In fact, this victory further emphasizes the military's resilience in competing peacefully. This is because democracy requires all succession of national leadership to be carried out periodically, regularly, and constitutionally. Thus, the elected leader is the people's choice. This is because the people are the owners of sovereignty as well as the source of political legitimacy.